The influence of wordwall game-based learning on higher-order thinking skills (hots) on water cycle materials - Kusumaningtyas, Anisa Wahyu; Yuniawatika, Yuniawatika; Utama, Candra (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
This research aims to determine the effect of word wall game-based learning on elementary school students' high-level thinking abilities on the water cycle material. This research uses a quantitative experimental type approach. The experiment chosen was a pre-experiment. This research was conducted with a sample of 21 children. The data collection technique uses tests and interviews. This test instrument will give students 6 HOTS questions. This question measures higher-order thinking Skills (HOTS) in the cognitive domain. Then, the data was analyzed using SPSS 26 with a normality test as a requirement for the paired sample t-test because the data was normally distributed. This research shows that word wall game-based learning influences elementary school students' HOTS on the water cycle material. That is shown by the results of the Sig paired sample t-test. (2-tailed) is 0.005 < 0.05. Teachers should learn using STEAM, especially by integrating technology using wordwalls. That is because there is a good influence of using word walls on elementary school students' HOTS.